The Influence of EFL Teachers’ Educational Beliefs on Classroom Practices - Messaouda BENDAHMANE (Altralang Journal, 2023)
Teaching English as a foreign language is given a vital concern in the Algerian field of education due to the major role English plays in the modern world. Many research papers have been devoted to find ways to make the process of teaching/ learning English successful and evidently found that the educational beliefs or the conceptions teachers hold about teaching and learning have a direct influence on shaping teachers’ classroom practices and figuring their students’ learning experience. Many research papers have been devoted to find ways to make the process of teaching/ learning English successful and evidently found that the educational beliefs or the conceptions teachers hold about teaching and learning have a direct influence on shaping teachers’ classroom practices and figuring their students’ learning experience. This study is an attempt to investigate Algerian teachers’ conceptions of teaching and learning and the potential relationship existing between these conceptions and the teaching approaches. To reach this aim, ten (10) teachers of English have participated in the study. The data were collected through classroom observation, the Conceptions of Teaching and Learning Questionnaire (CTLQ) and the Approaches to Teaching Inventory (ATI).  The results revealed teachers’ dominant conceptions and prevailing beliefs about teaching and learning and showed the salient impact these conceptions have on their teaching approaches. The study concludes with some pedagogical implications addressed to provide policymakers with insightful information about the current educational practices and the EFL contemporary learning setting aiming to inform and enhance pre-service teachers’ education program as well as in-service teachers’ professional training and development.